Hubungan Kreativitas Guru Dengan Motivasi Belajar Dan Hasil Belajar Siswa Kelas IV Di SDN Maospati 1 (Eduscotech, 2024)
This study aims to determine the relationship between teacher creativity and learning motivation and learning outcomes of fourth-grade students at SDN Maospati 1. Teacher creativity is one of the important factors in the learning process that can create an interesting, enjoyable learning atmosphere and motivate students to be more active in participating in learning. This study uses a quantitative approach with a correlational design. The population in this study were all fourth-grade students, and the sampling technique used purposive sampling. The instruments used were questionnaires to measure teacher creativity and student learning motivation, as well as documentation of grades to determine learning outcomes. The data obtained were analyzed using the Pearson Product Moment correlation technique and multiple regression. The results of the study showed that there was a positive and significant relationship between teacher creativity and student learning motivation. In addition, a significant relationship was also found between teacher creativity and student learning outcomes. Learning motivation was also proven to have a significant relationship with student learning outcomes. Simultaneously, teacher creativity and learning motivation contribute to improving student learning outcomes. Thus, this study confirms the importance of the role of teacher creativity in improving student motivation and learning outcomes. These findings recommend the need for teacher professional development in the aspect of learning innovation in order to optimally encourage student academic achievement.